The olive oil phenolic (−)-oleocanthal modulates estrogen receptor expression in luminal breast cancer in vitro and in vivo and synergizes with tamoxifen treatment - Ayoub, Nehad M. (Eur J Pharmacol, 2017)
Luminal breast cancer represents a therapeutic challenge in terms of aggressive disease and emerging resistance to targeted therapy. (−)-Oleocanthal has demonstrated anticancer activity in multiple human cancers. The goal of this study was to explore the effect of (−)-oleocanthal treatment on growth of luminal breast cancer cells and to examine the effect of combination of (−)-oleocanthal with tamoxifen. Results showed that (−)-oleocanthal inhibited growth of BT-474, MCF-7, and T-47D human breast cancer cells in mitogen-free media with IC(50) values of 32.7, 24.07, and 80.93 μM, respectively. Similarly, (−)-oleocanthal suppressed growth of BT-474, MCF-7, and T-47D cells in 17β-estradiol-supplemented media with IC(50) values of 22.28, 20.77, and 83.91 μM, respectively. Combined (−)-oleocanthal and tamoxifen treatments resulted in a synergistic growth inhibition of BT-474, MCF-7, and T-47D cells with combination index values of 0.65, 0.61, and 0.53 for each cell line, respectively. In-silico docking studies indicated high degree of overlapping for the binding of (−)-oleocanthal and 17β-estradiol to estrogen receptors, while (−)-oleocanthal and tamoxifen have distinguished binding modes. Treatment with 5 mg/kg or 10 mg/kg (−)-oleocanthal resulted in 97% inhibition of tumor growth in orthotopic athymic mice bearing BT-474 tumor xenografts compared to vehicle-treated animals. (−)-Oleocanthal treatment reduced total levels of estrogen receptors in BT-474 cells both in vitro and in vivo. Collectively, (−)-oleocanthal showed a potential beneficial effect in suppressing growth of hormone-dependent breast cancer and improving sensitivity to tamoxifen treatment. These findings provide rational for evaluating the effect of (−)-oleocanthal in combination with endocrine treatments in luminal breast cancer.